Предмет: Математика, автор: rusl4n666

2. Упростить выражение
а) 4(a-b-c)
б) 5(p+3)-2(p-2)
в) 0,2(-7s+5)+4(0,2s-2)
г) (12x-42) 1/6-3/4(-8x+12)


P.S 1/6 и 3/4 - дроби​

Ответы

Автор ответа: jekadva
4

Ответ:

Пошаговое объяснение:

а) 4(a-b-c)  = 4a - 4b - 4c

б) 5(p+3)-2(p-2)  = 5p + 15 - 2p + 4 = 3p + 19

в) 0,2(-7s+5)+4(0,2s-2)  = -1,4s + 1 + 0,8s - 8 = -0,6s - 7

г) (12x-42) 1/6-3/4(-8x+12) = 2x - 7 + 6x - 9 = 8x - 16

Автор ответа: Neyo002
1

Ответ:

а) 4а-4b-4c

б) 5p+15-2p+4= 3p+19

в) -1,4s+1+0,8s-8=-0,6s-7

г) 2х-7+6х-9=8х-16

Похожие вопросы
Предмет: Математика, автор: lawy